2009
DOI: 10.1002/ptr.2822
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the ameliorative potential of Punica granatum in dextran sulfate sodium induced ulcerative colitis in mice

Abstract: The present study was designed to investigate the ameliorative potential of Punica granatum in dextran sulfate sodium (DSS) induced ulcerative colitis. DSS (2%) was administered orally in drinking water for 7 days to induce ulcerative colitis. The extent and severity of ulceration was analysed macroscopically, histopathologically and using a disease activity index. Myeloperoxidase (MPO), a specific marker of inflammation; histamine, a marker of mast cell degranulation; superoxide anion generation and, lipid pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 42 publications
(54 reference statements)
4
65
0
2
Order By: Relevance
“…Our results are in agreement with previous reports from Ogawa et al [15] and Singh et al [16] with microspheres of ellagic and an ellagic acid rich fraction of Punica granatum extract in dextran sulphate sodium-induced colitis. In a similar way, there has also been described the protective effect of ellagic acid on gastric damage induced in ischemic rat stomachs following ammonia or reperfusion [26].…”
Section: Page 15 Of 37supporting
confidence: 94%
See 1 more Smart Citation
“…Our results are in agreement with previous reports from Ogawa et al [15] and Singh et al [16] with microspheres of ellagic and an ellagic acid rich fraction of Punica granatum extract in dextran sulphate sodium-induced colitis. In a similar way, there has also been described the protective effect of ellagic acid on gastric damage induced in ischemic rat stomachs following ammonia or reperfusion [26].…”
Section: Page 15 Of 37supporting
confidence: 94%
“…Previous reports, have documented that microspheres of ellagic acid [15] and a Punica granatum extract in addition to its ellagic acid rich fraction [16] decreased the degree of inflammation associated with experimental dextran sulphate sodium (DSS)-induced colitis. Intra-colonic administration of trinitrobenzene sulfonic acid (TNBS) is one of standardized methods to produce an experimental model of IBD, which closely mimic the clinical and morphological features of IBD in particular Crohn's disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has antibacterial, anti-inflammatory, anti-diabetic effects and is cardio-protective (161-163). Singh et al (164) explored the effect of Punica granatum extract and its component, ellagic acid, in the DSS-induced colitis mouse model and found significant attenuation of colonic inflammation. Mast cell degranulation, which releases various inflammatory mediators, including histamine, has been implicated in the pathogenesis of ulcerative colitis and the use of mast cell stabilizers have been documented to attenuate the severity of ulcerative colitis in humans (165).…”
Section: Pomegranatementioning
confidence: 99%
“…Mast cell degranulation, which releases various inflammatory mediators, including histamine, has been implicated in the pathogenesis of ulcerative colitis and the use of mast cell stabilizers have been documented to attenuate the severity of ulcerative colitis in humans (165). Singh et al (164) found that Punica granatum extract and its ellagic acid component had anti-ulcerative effects comparable to sodium cromoglycate (mast cell stabilser) and sulphasalazine (standard first line treatment for ulcerative colitis).…”
Section: Pomegranatementioning
confidence: 99%
“…Various plantsare also reported to be useful in IBD due to their immune modulatory antiulcerogenic property and anti-inflammatory property. [6][7][8][9][10] The plant Ricinus communis belongs to the family Euphorbiaceae. It is also known as castor in English, erand in Hindi, erendo and ereandi in Guajarati.…”
Section: Introductionmentioning
confidence: 99%